ETHICS OF ORGAN DONATION AND TRANSPLANTATION - Michael, Biju (Asian Horizons, 2013)
Biotechnology is revolutionizing medical practice throughout the world. The growth of biotechnology in Asia is phenomenal. India is amongst the top 12 biotech destinations in the world and second in Asia. In 2013 the market size of Indian biotechnology industry was $4.3 billion and is expected to rise to $11.6 billion by 2017. Biopharma export revenues contributed to 64.5% of total export revenues of the industry and registered 25% growth in 2013.1 Biocon Limited, a company from Bengaluru, India achieved 6th rank among Global ‘Top Twenty Employers’ list for the Bio-Pharma sector in the list published by ‘Science’ Magazine in 2013.